Mediastinal abscess complicating esophageal dilatation: a case report - Doaa M. Magdy; Shereen Farghaly; Ahmed Metwally (The Egyptian Journal of Bronchology, 2019)
Abstract Mediastinal abscess is a rare yet emergent infectious complication of the thoracic cavity following balloon dilatation of the esophagus. Early diagnosis and management could avoid its poor outcome. A 20-year-old man with esophageal stricture underwent balloon dilatation. A mediastinal abscess developed 2 weeks after procedure. Computed tomographic chest helped in diagnosis and guiding approach of management. Surgical drainage and debridement of the abscess were performed. Surgical treatment combined with systemic antibiotics was effective, leading to remission of the abscess. Mediastinal abscess should be considered as a possible infectious complication after upper endoscopy. Computed tomographic scan is a mandatory imaging modality to enable early diagnosis. Aggressive treatment including surgical drainage combined with medical management is the treatment of choice that may prevent catastrophic outcome.